Non-Euclidean geometry model for chemo-mechanical coupling in self-assembled polymers towards dynamic elasticity - Xing, Ziyu (2023)
Self-assembly plays a fundamental role to determine thermodynamic properties of polymer systems, e.g., resulting in the formation of dynamically cross-linked networks with varied elasticity. However, the working principle of chemo-mechanical coupling between the self-assembly and elasticity of polymers is complex and has not been well understood. In this study, a non-Euclidean geometry model incorporating thermodynamics of microphase separation is proposed to understand the chemo-mechanical coupling in self-assembled triblock polymers. The thermodynamic separation of microphases, which is resulted from the self-assembly of polymeric molecules, is formulated using a non-Euclidean geometry equation, of which the geometrical parameters are applied to characterize the topologies of self-assembled and cross-linked networks. The non-Euclidean geometry model is further employed to describe chemo-mechanical coupling between the self-assembled network and dynamic elasticity of the triblock polymers, based on the rubber elasticity theory. Effectiveness of the proposed model is verified using both finite-element analysis and experimental results reported in literature. This study provides a new geometrical approach to understand the mechanochemistry and thermodynamics of self-assembled block polymers.